Imbuhan Inulin Dan Enzim Papain Dalam Ransum Protein Dan Kalsium Mikropartikel Terhadap Produksi Daging Broiler - Lilik Krismiyanto; Nyoman Suthama; Bambang Sukamto; Amalia Nabila Ramadhani (Politeknik Negeri Jember, 2022)
A study was conducted to evaluate the effect of adding inulin from dahlia tube extract (DTE) and papain enzyme in the feed using protein and calcium microparticles on nutrient absrorption (protein and calcium), nutrient content (protein and calcium content) meat and meat weight on broiler. A total of 200 one-day-old unsex broiler chicks with feeding of treatment 8 days old with an average body weight 137.63±12.03 g. The experiment consisted of completely randomized design with 4 treatment and 5 replice, each 10 bird. The treatment applied were P0: feed with microparticle protein and calcium, P1: P0+DTE 1.17%, P2: P0+enzim papain 0.15%, dan P3: P0+DTE 1.17%+papain enzyme 0.15%. The parameters observed were protein and calcium absrorption, meat protein and calcium content, and meat weight. The data were processed based on analysis of variance followed by Duncan's multiple area test at the 5% level. The results showed that the addition of inulin and papain enzymes in the ration containing protein and calcium microparticles had a significant effect (p<0.05) on protein and calcium absorption, protein and calcium content of meat, and weight of broiler meat. The conclusion, a mixture of inulin from 1.17% DTE and 0.15% papain enzyme (P3) in the feed using a protein source and calcium microparticles resulted in the best nutrient intake and weight of broiler meat with the highest protein and calcium content.